Motif Pelaku Aborsi Di Kalangan Remaja Dan Solusinya (Studi Kasus Terhadap Mahasiswa di Universitas Trunojoyo Madura dengan Pendekatan Psikologi Komunikasi) - Sri Wahyuningsih; Yudho Bawono; Alifah Rahma Wati (Personifikasi: Jurnal Ilmu Psikologi, 2014)
AbstrakIn Indonesia, abortion is a common phenomenon, something that is usually done by people who do not want the fetus. From the WHO study estimated 20-60 percent of abortions in Indonesia is intentional abortion (induced abortion), because some of the underlying reasons. Most abortion clients are in the age range of 20-29 years. The researchers focused on adolescents (student) Trunojoyo University, who has had an abortion. From this number of abortions among adolescents in this study researchers tried to find a solution. Methods used this research is a type of qualitative research with a case study approach , the research object is the motive of the perpetrator to have an abortion while the subject is categorized adolescent students who have had abortions . Data collection is to indeepth interview, observation, and documentation. With purposive sampling technique. This study used a psychological approach to communication. In order for this study resulted in validity, researchers used triangulation of data validity. The results achieved in this study was the motive teen abortions are influenced by fear and shame to the immediate family (parents ), other families, community, neighbors, and friends . Construction of human motives that exist in this study are feeling fear, feeling shame, and feeling Compound. They are still sitting in college and do not want to interfere with her pregnancy so abortion is bieng happened. The abortion motif influenced by his girlfriend fiance or by taking special pills for abortion. The theory underlying this research is psychoanalysis Sigmund Freud’s theory that humans are driven by pent-up desires that Id. The solution offered in this study the presence of the psychology of communication according to Fisher's approach is acceptance of sensory stimuli, a process that mediates stimulus and response, response prediction and confirmation response. With the understanding, enjoyment, affect attitudes, good social relations, and actions that gave birth to adolescence with effective communication willing to accept moral education, premarital sex education, knowledge of the hazards of abortion, reproductive health, and doing activities that facilitate positive adolescent expression.